Effect of Noisy Galvanic Vestibular Stimulation on Ocular Vestibular-Evoked Myogenic Potentials to Bone-Conducted Vibration - Iwasaki, Shinichi; Karino, Shotaro; Kamogashira, Teru; Togo, Fumiharu; Fujimoto, Chisato; Yamamoto, Yoshiharu; Yamasoba, Tatsuya (Frontiers in Neurology, 2017)
Objective: Galvanic vestibular stimulation delivered as zero-mean current noise (noisy GVS) has been shown to improve static and dynamic postural stability probably by enhancing vestibular information. The purpose of this study was to examine the effect of an imperceptible level noisy GVS on ocular vestibular evoked myogenic potentials (oVEMPs) in response to bone-conducted vibration (BCV). Materials and methods: oVEMPs to BCV were measured during the application of white noise GVS with an amplitude ranging from 0 to 300 A (in RMS) in 20 healthy subjects. Artifacts in the oVEMPs caused by GVS were reduced by inverting the waveforms of noisy GVS in the later half of the stimulus from the one in the early half. We examined the amplitudes of N1 and N1-P1 and their latencies. Results: Noisy GVS significantly increased the N1 and N1-P1 amplitudes (p < 0.05) whereas it had no significant effects on N1 or P1 latencies (p > 0.05). Noisy GVS had facilitatory effects in 79% of ears. The amplitude of the optimal stimulus was 127 ± 14 A, and it increased the N1 and N1-P1 amplitude by 75.9 ± 15% and 47.7 ± 9.1%, respectively as compared with 0 A session (p < 0.05). Conclusions: Noisy GVS can increase the amplitude of oVEMPs to BCV in healthy subjects probably via stochastic resonance. The results of the present study suggest that noisy GVS may improve static and dynamic postural stability by enhancing the function of the vestibular afferents.